Health Behaviour in Family Planning Service Utilization and Policy Implications for Health Promotion in Indonesia. - Muhammad Ragil Dzihnu Sulkhi; Nur Rohmah; Ratno Ardianto (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The utilization of modern contraceptive methods has shown little improvement over the past decade. This stagnation indicating that barriers to Family Planning (FP) utilization may be rooted not merely in awareness or attitudes, but in access and service constraints within the health system. Objective : this study aims to examine the determinants of access and service barriers to family planning utilization in East Kalimantan, Indonesia. Research Methods/ Implementation Methods : This study is a cross-sectional design utilizing secondary data from the Indonesian Family Data Updating Survey 2024. A total of 217536 married women of reproductive age (15-49 years old) were included. Independent variables were age, marriage age, education level, insurance status, employment status, and ideal number of child. Dependent variable were barriers to family planning service. Chi-Square tests and Logistic Regression were included. Results : Of the 217,536 married women of reproductive age, the majority of respondents reported barriers categorized as non-access (57.4%) and (42.0%), only 0.6% reporting access barriers. Bivariate analysis established that all factors examined were significantly associated with the type of reported barriers. Service barriers were strongly determined by women aged 35–49 years (OR = 5.266), no formal education (OR = 1.155), informal occupation (OR = 1.178), and desiring more than two children (OR = 1.659). Access barriers was influenced by uninsured women (OR = 1.754) and no formal education (OR = 2.526). Conclusion/Lesson Learned : Policy interventions that enhance the availability, affordability, and quality of contraceptive services is essential to help the Indonesian Government designing integrated contraceptive programs to reduce inequalities in access and service barriers.